The Reflective Account of Transitioning Teaching Practices Across Instructional Modalities - Ben Vilkas; Brandon Juarez (Journal of Scholarly Engagement)
The current paper presents a reflective account of the transition of teaching practices across instructional modalities for one teacher educator in the Midwest region of the United States. The transition between modalities was deemed by college leadership as an essential means for aiding current students in adding additional educational endorsements to their degree programs. The teacher educator volunteered to transition this course across instructional modalities and decided to apply the principles found within Salomon and Perkins’ research pertaining to transfer of learning theory to reach his desired goal. The goal was to improve upon best practices already developed in the face-to-face modality when tasked with teaching the same course in the online modality. Specifically, the teacher educator introduced the concept of providing teacher candidates with assessment options that aligned with the curriculum objectives and promoted a sense of control for the teacher candidates. Three central challenges were explored through the reflective lens: communication of choices to teacher candidates specific to the asynchronous learning environment, development of manageable assessment options for a condensed online course timeframe, and the creation of communication protocols to support collaborative student engagement and provide support regarding assessment options. The qualitative nature of the study allowed for depth of analysis regarding how the teacher educator thought through and implemented revisions to the course with respect to transitioning the teaching practices to the online modality. The authors conclude the paper by providing recommendations surrounding the continued exploration of how the instructional modality plays part in the transitioning of teaching practices between modalities.